Self-employment and Subjective Well-Being - Martin Binder; Ann-Kathrin Blankenberg (Global Labor Organization (GLO), 2021)
Self-employment contributes to employment growth and innovativeness and many individuals want to become self-employed due to the autonomy and exibility it brings. Using "subjective well-being" as a broad summary measure that evaluates an individual's experience of being self-employed, the chapter discusses evidence and explanations why self-employment is positively associated with job satisfaction, even though the self-employed often earn less than their employed peers, work longer hours and experience more stress and higher job demands. Despite being more satisfied with their jobs, the self-employed do not necessarily enjoy higher overall life satisfaction, which is due to heterogeneity of types of self-employment, as well as motivational factors, work characteristics and institutional setups across countries.
Keywords: L26; J24; J28; 330; self-employment; entrepreneurship; subjective well-being; job satisfaction; life satisfaction